The Mind of a Child Molester. - Hammel-Zabin, Amy (Psychology Today, 2003)
In an article adapted from Conversations with a Pedophile: In the Interest of our Children, a convicted sex offender, who manipulated and molested more than 1,000 boys, analyses his behavior.